HUBUNGAN KADAR pH DARAH FUNICULUS UMBILICALIS DENGAN ASFIKSIA PADA BAYI BARU LAHIR DI RSUD CILACAP - Ramdani, Putri; Wijiastuti, Irma; ., Yuliawati; Susanti, Tri (Bidan Prada, 2013)
ABATRACT: BLOOD RELATIONS FUNICULUS UMBILICAL pH LEVELS WITH ASPHYXIA NEWBORN IN HOSPITAL CILACAP. The infant mortality rate based on data from the 2012 Demographic and Health Survey is 32/1000 live births, more than ¾ of infant mortality due to factor 1. Asphyxia, 2. And infection. Complications at birth, 3. LBW. The incidence of neonatal asphyxia in Cilacap General Hospital in May 2013 is 5:11%, end of June increased to 8, 87% of the total babies born. This research is analytic survey with cross-sectional approach. Population of 98 newborns with total sample sampling. Data analysis with Chi squere there is a relationship between umbilical cord blood pH with neonatal asphyxia (p value <0.005, meaning Ha received). Keywords: Cord Blood pH, Neonatal Asphyxia